The role of metacaspase 1 in Plasmodium berghei development and apoptosis. - Le Chat, L; Sinden, R; Dessens, J (2007)
The malaria parasite encodes a wide range of proteases necessary to facilitate its many developmental transitions in vertebrate and insect hosts. Amongst these is a predicted cysteine protease structurally related to caspases, named Plasmodium metacaspase 1 (PxMC1). We have generated Plasmodium berghei parasites in which the PbMC1coding sequence is removed and replaced with a green fluorescent reporter gene to investigate the expression of PbMC1, its contribution to parasite development, and its involvement in previously reported apoptosis-like cell death of P. berghei ookinetes. Our results show that the pbmc1 gene is expressed in female gametocytes and all downstream mosquito stages including sporozoites, but not in asexual blood stages. We failed to detect an apparent loss-of-function phenotype, suggesting that PbMC1 constitutes a functionally redundant gene. We discuss these findings in the context of two other putative Plasmodium metacaspases that we describe here.